2015
DOI: 10.1186/s12906-015-0649-9
|View full text |Cite
|
Sign up to set email alerts
|

Shenling Baizhu San supresses colitis associated colorectal cancer through inhibition of epithelial-mesenchymal transition and myeloid-derived suppressor infiltration

Abstract: AbstractsBackgroundShenling Baizhu San (SBS) is a well-known and classical Chinese medicine formula. It has been used for treatment of gastrointestinal disorders for about nine hundred years. Recent reports showed that it was effective in curing colitis and ameliorating the major manifestations of postoperational colorectal cancer (CRC). This study was to evaluate the effects of SBS on azoxymethane (AOM) and dextran sodium sulfate (DSS) induced colitis associated CRC (caCRC) and to analyze the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…Moreover, β-catenin and PCNA, as two important oncogenic transcription factors, have also been reported to play crucial roles during UC-associated colon carcinogenesis ( Cappello et al, 2003 ; Nelson and Nusse, 2004 ; Clevers, 2006 ; Georgescu et al, 2007 ). Our results clearly demonstrated that the expression levels of β-catenin and PCNA in colonic tissues were significantly up-regulated by AOM/DSS, which was in line with previous studies ( Lin et al, 2014 , 2015 ). Nevertheless, administration of celastrol significantly prevented up-regulation of these neoplastic markers.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, β-catenin and PCNA, as two important oncogenic transcription factors, have also been reported to play crucial roles during UC-associated colon carcinogenesis ( Cappello et al, 2003 ; Nelson and Nusse, 2004 ; Clevers, 2006 ; Georgescu et al, 2007 ). Our results clearly demonstrated that the expression levels of β-catenin and PCNA in colonic tissues were significantly up-regulated by AOM/DSS, which was in line with previous studies ( Lin et al, 2014 , 2015 ). Nevertheless, administration of celastrol significantly prevented up-regulation of these neoplastic markers.…”
Section: Discussionsupporting
confidence: 93%
“…Our results disclosed that CRC patients with low E-cadherin levels had a poorer 5-year OS rate, while loss of Vimentin could lead to an improved clinical outcome in CRC. All these results were consistent with the predictions of previous studies, which supported the role of EMT in CRC progression, particularly the changes of epithelial or mesenchymal traits during EMT [24,25]. CMTM proteins contain a MARVEL domain, which is involved in many essential cellular processes including tumor suppression.…”
Section: Discussionsupporting
confidence: 92%
“…Colorectal cancer, accompanied by intestinal microflora disorders, inflammation, metabolic dysfunction symptoms, and invasion of pathogens, remains the third most commonly diagnosed cancer and the fourth leading cause of cancer-related mortality worldwide [ 1 , 2 , 3 ]. Besides surgery, chemotherapy appears to be a primary therapeutic strategy for colorectal cancer largely due to the fact that most patients present at diagnosis with unresectable or metastatic disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%